EXAMINING THE FACTORS INFLUENCING THE SUCCESS OF MOBILE MONEY IN AFGHANISTAN - MANSSOORI, JALATKHA; AL-HUSSAINI, ABULFATHI IBRAHIM SALEH; Abubakar, Adamu (KICT, IIUM, 2021)
The advancement and rapid development of mobile money has created extraordinary opportunities for poor people in developing countries to help contribute in the development of the economy. Mobile money has formed an effective and efficient mechanism for the electronic transaction of money. Regardless of the remarkable improvement in the recent decades, the economy of Afghanistan still has not improved. Citizens of this country are some of the poorest in the world. Due to the system being undigitized and corruption, there is distrust among banks, bribery, graft of employee salaries by their supervisors and high costs of currency transport. There is very limited accessibility to basic financial services due to lack of e-transaction and banking services. The introduction of mobile money as an electronic transfer of money can be a partial solution to the problems being faced in Afghanistan. However, lack of system quality, information quality and service quality assurances is an essential problem to the success and usage of mobile money which need to be improved. This paper aims to determine the impact and influence of system, information, and service qualities on the use of mobile money. The study can help unbanked citizens to access basic financial services through mobile money. It can also help owners assess mobile money to improve the system, information, and service qualities. The DeLone and McLean IS Success Model has been adapted as theoretical method for this paper to evaluate the success of mobile money services based on four influencing factors as the main objectives of the paper. Based on a review of the literature, a quantitative paper method was applied for data collection through an online survey questionnaire. The data has been randomly collected from the users of mobile money in Afghanistan. The data has been analyzed through SPSS and PLS-SEM model. PLS-SEM analyses were performed for the result of the data analysis. Based on the analysis of the responses of the participant, system quality, information quality, service quality and customer value were seen to have significant and positive impact on the success of mobile money services in Afghanistan.